Hydrogen separation by thin vanadium-based multi-layered membranes. (8th February 2018) - Fasolin, Stefano; Barison, Simona; Boldrini, Stefano; Ferrario, Alberto; Romano, Matteo; Montagner, Francesco; Miorin, Enrico; Fabrizio, Monica; Armelao, Lidia
Abstract: Thanks to their high hydrogen permeability, vanadium based alloys can be a valuable and sustainable alternative to palladium alloys, commonly employed in commercial membranes for hydrogen purification/separation. In this work, the unprecedented deposition of micrometric vanadium-based multilayers and their investigation as hydrogen selective membranes have been reported. In particular, this work describes the use of High Power Impulse Magnetron Sputtering, a technique easily scalable also for complex geometries, for the deposition of dense and crystalline Pd/V93 Pd7 /Pd multilayers with total thickness <7 μm onto porous alumina. These membranes showed high hydrogen fluxes in the 300–400 °C range, up to 0.26 mol m −2 s −1 at 300 kPa pressure difference and 375 °C, as well as an unexpected and significant resistance to hydrogen embrittlement and to syngas in operating conditions. Highlights: We developed thin Pd/V93 Pd7 /Pd multi-layers on porous alumina for hydrogen separation. HiPIMS was used for the first time to produce membranes for hydrogen separation. The content of Pd is low enough to have sustainable and cheap membranes. Hydrogen fluxes up to 0.26 mol m −2 s −1 at ΔP of 300 kPa and 375 °C were measured. Good resistance to embrittlement and syngas was ascertained.